Total Quality Management and Business Excellence: The Best Practices at Toyota Motor Corporation. - Sorin-George Toma; Shinji Naruo (Amfiteatru Economic)
Today’s rough competition at a global level in all spheres of activity imposes companies worldwide to make sustained efforts in order to improve their products, services and processes. The automotive industry has always provided valuable examples of companies that achieved business excellence by putting quality at the core of their production system such as Toyota Motor Corporation. It has continuously designed, implemented and developed the Toyota Production System that influenced the emergence of the business excellence models. The paper aims to highlight the relationship between the concepts of total quality management and business excellence, and to identify and analyze the best practices related to them at Toyota Motor Corporation, a leader of automotive industry. The information obtained through the direct and personal observation method and from multiple secondary sources of data was collected, processed and analyzed in order to achieve the objectives of the paper. The main results show that the best practices of Toyota Motor Corporation related to total quality management and business excellence derive from the Toyota Production System and these practices are to be found in the attributes of business excellence.